PENGGUNAAN GAME EDUKATIF WORDWALL DALAM PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN MINAT DAN KETERAMPILAN LITERASI SISWA KELAS V SD - Winarni; Bambang Putut Setiyadi, Dwi; Mulyatno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low active participation and less than optimal literacy skills of fifth-grade students in learning. The study aims to describe the implementation and assess the impact of Wordwall educational games in interactive learning on students' learning interest and reading literacy skills. A Classroom Action Research (CAR) method with two cycles was employed, involving 11 fifth-grade students at SD Negeri 5 Pracimantoro. Data collection techniques included observation, interviews, questionnaires, literacy tests, and documentation. The results showed a significant increase in student learning interest, from the pre-cycle category dominated by